PENGARUH MOTIF MENONTON TAYANGAN ONE STOP FOOTBALL TRANS 7 TERHADAP KEPUASAN SISWA TIGA NAGA FOOTBALL ACADEMY AND SOCCER SCHOOL PEKANBARU - Feryandes Rozialta; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Progress of mass media, especially the television media now is increasingly rapidly, where broadcast television has allowed the general public can quickly and easily find a variety of recent developments that occurred in various parts of the world. In general everyone likes sportaiment program (Sport News). One Stop Football Trans 7 is a favorite sport news with different characteristic presentation. In Uses and Gratification theory, audience basicly using the mass media based on certain motives, which the media considered tring to meet the needs of the audience called as an effective media. The purpose of this research is to determine how much influence the motive watching One Stop Football Trans 7 against satisfaction of students at Tiga Naga Football Academy and Soccer School Pekanbaru.The method used in this research is quantitative method of explanation, the data collection through questionnaires. Location of the research conducted at Tiga Naga football Academy and Soccer School Pekanbaru. The total sample of this study are 96 respondents. The sampling techniques is using census. To determine how much influence the two variables, researchers used a simple linear regression analysis. To Questionnaire data processing, used program Statistical product and Service Solutions (SPPS) Windows version 20.Based on simple linear regression result for this study, the regression ceoffecient values obtained in this study is Y = 2,135 + 0,942 X with significance level of 0,003 and smaller than a = 0.5. according to based on determination test, the result amounted to 79,7% with high category. This means there is influence between watching One Stop Football Trans 7 against satisfaction of students Tiga Naga Football Academy and Soccer School Pekanbaru. The percentage shows that the satisfaction of watching the respondents can be fullfil. That means Ho is rejected and Ha accepted.Keywords : TV Program,Trans 7, and Tiga Naga Football Academy